In Vitro Hemocompatibility and Genotoxicity Evaluation of Dual-Labeled [99mTc]Tc-FITC-Silk Fibroin Nanoparticles for Biomedical Applications - María Alejandra Asensio Ruiz; Ángela Alonso García; María de la Luz Bravo-Ferrer Moreno; Iria Cebreiros-López; José Antonio Noguera-Velasco; Antonio Abel Lozano-Pérez; Teresa Martínez Martínez (MDPI AG, 2023)
Nuclear imaging is a highly sensitive and noninvasive imaging technique that has become essential for medical diagnosis. The use of radiolabeled nanomaterials capable of acting as imaging probes has shown rapid development in recent years as a powerful, highly sensitive, and noninvasive tool. In addition, quantitative single-photon emission computed tomography (SPECT) images performed by incorporating radioisotopes into nanoparticles (NPs) might improve the evaluation and the validation of potential clinical treatments. In this work, we present a direct method for [99mTc]Tc-radiolabeling of FITC-tagged silk fibroin nanoparticles (SFN). NPs were characterized by means of dynamic light scattering and scanning electron microscopy. In vitro studies were carried out, including the evaluation of stability in biological media and the evaluation of hemocompatibility and genotoxicity using the cytokinesis block micronucleus (CBMN) assay. The radiolabeling method was reproducible and robust with high radiolabeling efficiency (∼95%) and high stability in biological media. Hydrodynamic properties of the radiolabeled NPs remain stable after dual labeling. The interaction of SFN with blood elicits a mild host response, as expected. Furthermore, CBMN assay did not show genotoxicity induced by [99mTc]Tc-FITC-SFN under the described conditions. In conclusion, a feasible and robust dual-labeling method has been developed whose applicability has been demonstrated in vitro, showing its value for further investigations of silk fibroin NPs biodistribution in vivo.